Environmental Bioengineering Volume 11 - Wang, Lawrence K.; Tay, Joo-Hwa.; Tay, Stephen Tiong Lee.; Hung, Yung-Tse.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2010)
The impact of pollution on the environment has emerged as a particularly critical area of research in recent years. The Handbook of Environmental Engineering is a collection of methodologies that study the effects of pollution and waste in their three basic forms: gas, solid, and liquid. In this invaluable volume, Volume 11: Environmental Bioengineering, expert researchers explore the engineering applications of biotechnologies.A sister volume to Volume 10, Environmental Biotechnology, this work introduces such essential and varied topics as land disposal of biosolids, heavy metal removal by crops, pre-treatment and bio-treatment of sludge, fermentation of kitchen garbage, phyotoremediation for heavy metal contaminated soils, bioremediation, wetland treatment, biosorption of heavy metals, and rotating biological contactors (RBC) for carbon and nitrogen removal. A critical volume in the Handbook of Environmental Engineering series, chapters employ methods of practical design and calculation illustrated by numerical examples, include pertinent cost data whenever possible, and explore in great detail the fundamental principles of the field. Comprehensive and groundbreaking, Volume 11: Environmental Bioengineering presents innovative solutions to some of the most recent and significant pollution problems that the world is facing today.
Treatment and Disposal of Biosolids -- Ultrasound Pretreatment of Sludge for Anaerobic Digestion -- Solubilization of Sewage Sludge to Improve Anaerobic Digestion -- Applications of Composted Solid Wastes for Farmland Amendment and Nutrient Balance in Soils -- Biotreatment of Sludge and Reuse -- Kitchen Refuse Fermentation -- Heavy Metal Removal by Crops from Land Application of Sludge -- Phytoremediation of Heavy Metal Contaminated Soils and Water Using Vetiver Grass -- Bioremediation -- Wetlands for Wastewater Treatment -- Modeling of Biosorption Processes -- Heavy Metal Removal by Microbial Biosorbents -- Simultaneous Removal of Carbon and Nitrogen from Domestic Wastewater in an Aerobic RBC -- Anaerobic Treatment of Low-Strength Wastewater by a Biofilm Reactor -- Biological Phosphorus Removal Processes -- Total Treatment of Black and Grey Water for Rural Communities -- Anaerobic Treatment of Milk Processing Wastewater -- Biological Wastewater Treatment of Nutrient-Deficient Tomato-Processing and Bean-Processing Wastewater -- Animal Glue Production from Skin Wastes -- An Integrated Biotechnological Process for Fungal Biomass Protein Production and Wastewater Reclamation -- Algae Harvest Energy Conversion -- Living Machines -- Global Perspective of Anaerobic Treatment of Industrial Wastewater.
Keywords: Environmental sciences; Environment; Environment, general